Cooperative Catalysis for Selective Alcohol Oxidation with Molecular Oxygen. Issue 35 (27th July 2016) - Slot, Thierry K.; Eisenberg, David; van Noordenne, Dylan; Jungbacker, Peter; Rothenberg, Gadi
Abstract: The activation of dioxygen for selective oxidation of organic molecules is a major catalytic challenge. Inspired by the activity of nitrogen‐doped carbons in electrocatalytic oxygen reduction, we combined such a carbon with metal‐oxide catalysts to yield cooperative catalysts. These simple materials boost the catalytic oxidation of several alcohols, using molecular oxygen at atmospheric pressure and low temperature (80 °C). Cobalt and copper oxide demonstrate the highest activities. The high activity and selectivity of these catalysts arises from the cooperative action of their components, as proven by various control experiments and spectroscopic techniques. We propose that the reaction should not be viewed as occurring at an 'active site', but rather at an 'active doughnut'–the volume surrounding the base of a carbon‐supported metal‐oxide particle. Abstract : Mmm…catalytic doughnuts : The combination of the oxygen reduction properties of nitrogen‐doped carbons with copper‐ or cobalt‐oxide catalysts creates cooperative catalytic regions or ′active doughnut′ sites. These sites enable selective oxidation of alcohols (e.g., cinnamyl alcohol to cinnamaldehyde) using dioxygen, with good conversion and excellent selectivity.